Evaluation of Extra-Cranial Carotid Arteries by Digital Subtraction Angiogram (DSA) in Stroke Patients in a Tertiary Care Hospital - Ahmed, Reza Nasim; Begum, Most Mahmuda; Rashid, Md Abdur; Azam, Md Shafiul; Fatematujjahura, Mst; Kabir, Md Raseul (Medicine Today, 2022)
Introduction: Carotid artery stenosis is one of the important causes of ischemic stroke. This may be diagnosed by Doppler Ultrasound and Digital Subtraction Angiogram (DSA) both of which have some advantages and disadvantages. Objective: The aim of this study was to assess extra-cranial carotid artery with the help of DSA among patients of ischemic stroke and transient ischemic attack (TIA). Materials and Methods: This observational cross sectional study was conducted in the Department of Neurology in Bangabandhu Sheikh Mujib Medical University (BSMMU) Dhaka from July 2013 to June 2015 for a period of two years. This study included a total of 50 patients. Diagnostic performance test of DSA was done at 50%, 50-69%, 70-99%, 100% cut off point of stenosis of right internal carotid artery (RICA) and Left internal carotid artery (LICA). Results: The mean age of cases was 61 ± 11.42 years. Out of 50 vessels, maximum cases were diagnosed as <50% stenosis of carotid artery (26 cases of RICA, 23 cases of LICA. Out of 50 vessels, 50%-69%, 70 but _ less than near occlusion and total occlusion were found among 10, 10, 4 vessels in RICA and 10, 9, 8 vessels in LICA respectively. The present study showed that 50 vessels of RICA was measured by DSA and diagnosed 28 (56%), 10 (20%), 7 (14%) and 5 (10%) carotid vessels as _ 50%, 50-69%, _70% but less than total occluded and total occluded cases respectively. This study also showed that 50 vessels of LICA was measured by DSA and diagnosed 23 (56%), 12 (24%), 8 (16%), 7 (14%) carotid vessels as _ 50%, 50-69%, _ 70% but less than total occluded and total occluded cases respectively. Conclusion: DSA as the gold standard has amply been performed in most diagnostic circumstances of carotid artery stenosis. So, the present study was done to evaluate extra cranial carotid arterial system by DSA in stroke patients in Bangladesh. Medicine Today 2022 Vol.34(2): 121-124